High-sensitivity multi-channel DPSK system with real-time phase lock controller for free-space optical communication - Gao, Duorui; Li, Tianlun; Xie, Zhuang; Meng, Jiacheng; Jia, Shuaiwei; Bai, Zhaofeng; Wang, Wei; Xie, Xiaoping (Frontiers in Physics, 2022)
To overcome the power jitters in satellite-to-ground communications caused by atmospheric turbulence, a type of DPSK free-space communication system, assisted by a self-designed real-time phase lock controller, has been established. The system can effectively compensate for power swings in communication links and hence achieve high sensitivity. The wavelength division multiplexing technique is applied to a four-channel DPSK system to provide greater link capacity. With the data rate of a single channel as 2.5 Gbps and unencoded BER as 1 × 10–3, reception sensitivity has been obtained at −53.58 dBm (13.69 photons/bit), −53.59 dBm (13.66 photons/bit), −53.61 dBm (13.59 photons/bit), and −53.63 dBm (13.53 photons/bit) for each independent channel, respectively. The gap between our sensitivity result and the theoretical limit has narrowed to about −3.5 dB. Simultaneously, the DPSK receiver, with our self-designed phase lock controller, has stabilized reception of optical power fluctuations that range from 0 to 40 dB. Additionally, the impact of a four-wave mixing effect on multi-channel system performance has been investigated in detail. Our experimental results present a novel solution for the superior performance of free-space communication links.